The influence of environmental cues on behavioral response: An assessment of the Protective Action Decision Model in the context of COVID-19 - Silver, Amber; Koyratty, Nadia; Penta, Samantha; Clay, Lauren (Wiley, 2025)
The Protective Action Decision Model has emerged within the literature as a theoretical model with promising predictive ability, particularly in the context of short‐term behavioral response and longer‐term hazard adjustments. However, the applicability of the model in the context of public health hazards is less certain. Accordingly, this research utilizes an online questionnaire instrument disseminated via Qualtrics to residents of New York State at three points in the COVID‐19 pandemic (October 2020, January 2021, and May–June 2021) to examine whether changes to the built environment (i.e., signs requiring masking, signs requiring social distancing, and presence of hand sanitizing stations) influenced threat perceptions (i.e., perception of severity and likelihood of infection), and in turn, behavioral responses (i.e., masking, social distancing, and hand sanitizing) at different points in time. The results demonstrate that changes in the built environment were positively associated with behavioral responses at different points in the pandemic, rather than being mediated through threat perception, as predicted by the Protective Action Decision Model (PADM). The paper concludes with a brief discussion of how these findings may guide future research on environmental cues, threat perceptions, and behavioral response to better understand protective action decision‐making in the context of an ongoing public health hazard.